Appreciable role of stratospheric polar vortex in the abnormal diffusion of air pollutant in North China in 2015/2016 winter and implications for prediction. (15th August 2021) - Huang, Wei; Yu, Yueyue; Yin, Zhicong; Chen, Haishan; Gao, Meng
Abstract: The longer predictability limit and downward impact on the extratropical circulations and weather have made the winter Stratospheric Polar Vortex (SPV) variability a new source for sub-seasonal prediction in extratropical wintertime. Using the PM2.5 observation data and high-resolution ERA5 reanalysis data during 2014–2019, we investigate the characteristics of SPV and its linkage to the tropospheric meteorological condition during the abnormal PM2.5 diffusion event in North China in 2015/2016 winter. Results show that this diffusion event includes two stages: rapid diffusion stage (December 22–28, 2015) and persistent diffusion stage (January 1–23, 2016). The tropospheric meteorological condition in both stages was characterized by enhanced northerlies over North China, which dominantly led to the anomalous PM2.5 concentration drop. An active coupling process between SPV and surface Arctic Oscillation (AO) is found at the persistent diffusion stage, rather than at the rapid diffusion stage. The amplified tropospheric waves associated with the negative AO in the end of December propagated upward and helped split the SPV into two sub-vortices respectively over North Atlantic and North Asia in the beginning of January; the SPV weakening signal then propagated downward, helping intensify the negative AO since January 11, which further strengthened the northerly as well as PM2.5 diffusion over the entire East Asia. This case study demonstrates that the stratosphere-troposphere coupling effectively favors and extend the duration of PM2.5 diffusion, and the weakening of SPV provides a long lead information (1–2 weeks) to the meteorological diffusion condition, thus showing appreciable potential for extending the predictability limit of meteorological diffusion condition in North China. Highlights: The PM2.5 diffusion event in North China includes a rapid- and a persistent-stage. Stronger low-level northerlies dominated the abnormal diffusion in both stages. Stratosphere-troposphere coupling extends diffusion duration in persistent stage. Weakening of stratospheric polar vortex can provide lead information for diffusion. Stratospheric polar vortex has potential for extended-range prediction of diffusion.